DETERMINAN TURNOVER INTENTION PERAWAT DI MASA PANDEMI COVID-19 - Fezi Waldeseska Aulia; Siti Rodiah; Wira Ramashar (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2022)
This study aims to examine the effect of work stress, job satisfaction and compensation on nurses' turnover intention during the covid-19 pandemic (case study of Pekanbaru Medical Center Hospital) partially and simultaneously. The population is nurses who work at Pekanbaru Medical Center Hospital. The sampling method in this study uses a non-probability sampling technique, namely a sampling method that does not provide opportunities or provide equal opportunities for each member of the population to be selected as a sample. The non-probability sampling method used is saturated sampling. The data analysis technique used is multiple linear regression analysis method with a significance level of 0.05. The questionnaires used in this study were 102 questionnaires. The results of this study indicate that work stress, job satisfaction and compensation affect the turnover intention of nurses during the COVID-19 pandemic.